Comparison of Cysteine Protease B Gene Expression between Clinical Isolates of Leishmania tropica, Leishmania major and Leishmania infantum - Elham Kazemirad; Hossien Reisi Nafchi; Alireza Latifi; Reza Raoofian; Mehdi Mohebali; Homa Hajjaran (Pasteur Institute of Iran, 2019)
Introduction: Leishmania cysteine protease B (CPB) is a parasite virulence factor that plays a vital role in host-parasitic interactions. Regarding the importance of the CPB gene, we used a quantitative real-time RT-PCR to investigate the expression of CPB in the Iranian isolates of different Leishmania species. Methods: In this study, 36 clinical samples were collected, out of which 29 belonged to cutaneous leishmaniasis (CL), 3 to viscerotropic leishmaniasis (VTL), and 5 to visceral leishmaniasis (VL) patients. Among CL isolates, 8 were Leishmania major, and 21 were Leishmania tropica, including 3 isolates from the lupoid type. After RNA extraction and cDNA synthesis, gene expression analysis was performed by qPCR. Results: Our results showed the highest expression of CPB in isolates of Leishmania infantum, followed by L. major and L. tropica. Among L. tropica isolates, in the lupoid forms, the mean expression of CPB was ≈6.4 times higher than that of non-lupoid isolates. In L. major isolates, a significant difference was observed between the level of gene expression and the duration of the infection. The expression level of CPB was associated with the severity of the infection in L. infantum isolates. Conclusion: The CPB gene expressed in all Leishmania species. The highest expression was in L. infantum species and the least expression in L. tropica. The transcript level of CPB increased in L. major isolates derived from patients with a higher number and duration of ulcers; however, further studies on more clinical samples are needed to explore our findings.